Rearrangement of allyl phenyl ether over Al-MCM-41 - Mathew, Nevin T.; Khaire, S.; Mayadevi, S.; Jha, Ratnesh Kumar; Sivasanker, S. (Journal of Catalysis, 2005)
Claisen rearrangement of allyl phenyl ether to o-allylphenol and a dihydrobenzofuran derivative was investigated over MCM-41 with different Si/Al ratios. Higher aluminum content, higher reaction temperatures, and longer run duration favor the formation of the ring compound 2,3-dihydro-2-methyl benzofuran. There is a close relationship between acidity and conversion, which suggests that the reaction occurs inside the large pores of MCM-41. The influence of temperature and catalyst Si/Al ratio on the reaction are examined by kinetic analysis, under the assumption of a first-order consecutive reaction. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: Al-MCM-41; allyl phenyl ether; Claisen rearrangement; Mesoporous material; molecular rearrangement; Solid acids

Synthesis of bismuth oxide nanoparticles using bismuth nitrate and urea - Jha, Ratnesh Kumar; Pasricha, R.; Ravi, V. (Ceramics International, 2005)
A mixture of bismuth nitrate and urea is taken in 1:5 molar ratio and heated on hot water bath. A precipitate is formed on evaporation of the water which on decomposition at 400 degrees C produces nanocrystalline Bi2O3 particles. Formation of nano crystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscopy (TEM) investigations revealed for these powders an average particle size of 50 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: calcination; Electron microscopy; X-ray methods

Textural/structural, stability and morphological properties of mesostructured silicas (MCM-41 and MCM-48) prepared using different silica sources - Gaydhankar, T. R.; Taralkar, U. S.; Jha, Ratnesh Kumar; Joshi, P. N.; Kumar, R (Catalysis Communications, 2005)
A series of MCM-41 and MCM-48 samples have been synthesized under hydrothermal and static conditions using different silica sources (fumed silica, silica sot and ethyl silicate) and characterized by powder XRD, scanning electron microscopy and N-2 adsorption. The silica source reactivity trend observed was as: ethyl silicate > fumed silica > silica sot. However, the extent of contraction caused by calcination, magnitude of the wall thickness and stability were found to depend not only upon the type of silica source used but also on the type of structure formed. Noticeable morphological differences were observed in case of only MCM-41 when silica sources were varied. © 2005 Elsevier B.V. All rights reserved.

Assembly of hydrothermally stable ethane-bridged periodic mesoporous organosilicas with spherical and wormlike structures - Shylesh, S.; Jha, Ratnesh Kumar; Singh, A. P. (Microporous and Mesoporous Materials, 2006)
Hydrothermally stable periodic mesoporous organosilicas with spherical as well as wormlike frame structures were synthesised by two different synthesis routes using the silsesquioxane precursor, 1,2-bis (triethoxy silyl) ethane (BTEE) and surfactant octadecyl trimethyl ammonium (ODTA), under basic conditions. The materials were characterized by PXRD, SEM, TEM, N-2 adsorption-desorption, FT-IR, Si-29 MAS NMR, C-13 CP MAS NMR and TG-DTA techniques. Characterization techniques revealed that the morphology of the hybrid material prepared from pure silsesquioxane precursor resulted in spherical particles while a combination of tetra ethyl orthosilicate and 1,2-bis (triethoxy silyl) ethane (90:10 ratio) resulted in materials having wormlike structures. Hydrothermal stability of the hybrid material was evaluated by refluxing the sample under boiling water for various time periods and was compared with that of a periodic mesoporous silica material, Si-MCM-41. Results showed that the hybrid material is stable up to 100 h in boiling water, with the existence of d(100) peak, while the mesopore structure of Si-MCM-41 get destroyed even after a 12 h reflux time. The improved hydrothermal stability of the hybrid material is related to the more hydrophobic environment induced inside the pore channels, due to the presence of integrating ethane groups in the wall channels. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: hybrid mesoporous materials; Hydrothermal stability; spherical particles; wormlike structures

Oxidation of ethyl benzene and diphenyl methane over ordered mesoporous M-MCM-41 (M = Ti, V, Cr): synthesis, characterization and structure-activity correlations - Jha, Ratnesh Kumar; Shylesh, S.; Bhoware, Shrikant S.; Singh, A. P. (Microporous and Mesoporous Materials, 2006)
Transition metals (M = Ti, V, Cr) were incorporated into the MCM-41 framework by surfactant-assisted direct hydrothermal (DHT) methods and were characterized in detail by XRD, N-2 adsorption-desorption, TG-DTG/DTA, SEM/TEM, DR UV-Vis, XPS and EPR. The structural regularity as well as the textural properties of the M-MCM-41 materials was confirmed by XRD, TEM and adsorption-desorption techniques. Nature of metal species and the percentage of framework as well as extra framework metal sites in the MCM-41 matrix are discussed in detail by various spectroscopic techniques. The catalytic activity as well as the selectivity of the M-MCM-41 catalysts were explored in the one-step liquid-phase oxidation reaction of ethyl benzene and diphenyl methane. Reaction data showed that the oxidation activity is more when H2O2 was used an oxidant, acetonitrile as solvent and V-MCM-41 as catalyst. However, the selectivity towards the desired keto derivatives (ethyl benzene to acetophenone and diphenyl methane to benzophenone) follows the order, Ti-MCM-41 > V-MCM-41 > Cr-MCM-41. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: diphenyl methane; Ethyl benzene; MCM-41; Oxidation

Structural evolutions of hydrothermally prepared mesostructured MCM-48 silica using differently manufactured amorphous silica powders - Taralkar, U. S.; Jha, Ratnesh Kumar; Joshi, P. N. (Journal of Non-Crystalline Solids, 2007)
The hydrothermal synthesis of Si-MCM-48 mesoporous molecular sieves was carried out using a ternary SiO2:CTAOH:H2O System wherein differently manufactured amorphous silica powders such as fumed silica (FMDS), spray dried precipitated silica (SDPS) and flash dried precipitated silica (FDPS) were used as silica source materials. The changes in structural/textural properties were evaluated using powder XRD, N-2 adsorption-desorption and scanning electron microscopy techniques. Studies on the progressive development of MCM-48 mesophases revealed that, the reactivity of the silica source follow the trend: FMDS > SDPS > FDPS. MCM-48 synthesized using low cost FDPS has exhibited thicker pore walls but poorer orderness, while MCM-48 prepared from relatively expensive FMDS has thinner pore walls and more ordered structure. Moreover, the extent of contraction caused by calcinations, agglomerate size and structural stability were found to depend on the reactivity of the silica source used. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: long-range order; micelles; scanning electron microscopy; silica; silicates; sol-gels (xerogels); X-ray diffraction

Low temperature synthesis and characterization of BiNbO4 powders - Radha, R.; Muthurajan, H.; Rao, N. Koteswara; Pradhan, Sivaram; Gupta, U. N.; Jha, Ratnesh Kumar; Mirji, S. A.; Ravi, V. (Materials Characterization, 2008)
BiNbO4 powders, a potential microwave dielectric ceramic were prepared by both coprecipitation and solid state techniques. In the former method, an aqueous ammonium hydroxide was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. It is observed that the co-precipitation produces BiNbO4 phase on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the case of solid state method. The phase contents and lattice parameters were studied by powder X-ray diffraction. The sequence of the reaction and phase evolution of BiNbO4 were also studied by the X-ray diffraction. The samples were characterized by the differential-thermal/thermo-gravimetric analyses and scanning electron microscopy techniques. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Low temperature synthesis of SrNb2O6 and SrTa2O6 using hydroxide precursor - Muthurajan, H.; Kumar, H. H.; Koteswara Rao, N.; Pradhan, Sivaram; Jha, Ratnesh Kumar; Ravi, V. (Materials Letters, 2008)
SrNb2O6 (SN) or SrTA(2)O(6) (ST) compounds were prepared at low temperatures for the first time from hydroxide precursors. A simple procedure of mixing commercially purchased strontium hydroxide and niobium (or tantalum) hydroxide thoroughly together and heating at a low temperature (<400 degrees C) produced SrNb2O6 (SN) or SrTa2O6 (ST) powders. This is the lowest temperature so far reported for the formation of these phases. These materials are potential candidates for ferroelectric and electro-optic applications. The reaction sequence and evolution of the phase formation were investigated by X-ray diffraction (XRD) studies. The average particle size and morphology of these powders were studied by scanning electron microscopy (SEM). (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray diffraction

Non-isothermal kinetic studies of the template decomposition from silicalite-1 framework-high temperature X-ray diffraction and thermogravimetric analysis - Bhange, Deu S.; Pandya, N. A.; Jha, Ratnesh Kumar; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
Non-isothermal decomposition of the tetrapropylammonium cations (TPA(+)) intercalated in silicalite-1 framework has been carried out using thermogravimetric (TG) analysis and high temperature powder X-ray diffraction (HTXRD) techniques. Conversion factor for template decomposition is calculated using two methods viz., % weight loss from the thermogravimetric analysis and changes in the intensities of the Bragg reflections 101/011 and 200/020 in the HTXRD patterns scanned at different temperatures (range 298823 K). The calculated apparent activation energy for template decomposition in air was 129 and 125 kJ mol(-1), respectively, for the two techniques TG and HTXRD, calculated using the Kissinger method. By Flynn-Wall-Ozawa approach of isoconversion, apparent activation energy for template decomposition in air was 123 and 124 U mol-1, respectively, for TG and HTXRD data. The reaction order was determined using the method of Kennedy and Clark and it is similar to 2 by both the techniques. The second order of template decomposition can be attributed to the fact that TPA+ is positioned in two different orientations inside the silicalite-1 framework. Template removal occurs with a contraction in unit cell dimensions. There is a decrease in the lattice parameters of the as-synthesized silicalite-1 sample after removal of template from the framework. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: HTXRD; non-isothermal kinetics; Silicalite-1

Novel hydroxide precursors for low temperature synthesis of selected ternary oxides - Muthurajan, H.; Rao, N. Koteswara; Gupta, U. N.; Pradhan, Sivaram; Jha, Ratnesh Kumar; Kumar, H. H.; Mirji, S. A.; Ravi, V. (Materials Research Bulletin, 2008)
A novel method of using hydroxide precursors to reduce the synthesis temperature for few selected ternary oxides has been presented here. This technique is very useful and advantageous when the ternary oxides contain an alkaline earth element. The selected compositions for this method are BaCeO3 (BC), BaBiO3 (BB), La0.7Sr0.3CoO3 (LSCO) and BaBi2Nb2O9 (BBN). Commercially purchased strontium (or barium) hydroxide and freshly prepared lanthanum, cobalt, bismuth and niobium hydroxides were mixed thoroughly in stoichiometric ratio and heated at different temperatures ranging from 100 to 700 degrees C for 10 h for corresponding compositions. The sequence of the reaction and evolution of the product phase were studied by the X-ray diffraction (XRD) studies. The phase purity and lattice parameters were also determined by XRD investigations. All the product phases in each case were formed at relatively low temperature than when they were prepared by co-precipitation or solid state method. The morphology and average particle size of these powders were investigated by scanning electron microscopy (SEM). (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Novel synthesis of SrBi2Nb2O9 powders from hydroxide precursors - Gupta, Upendra Nath; Rao, Koteswara; Pradhan, Sivaram; Jha, Ratnesh Kumar; Muthurajan, Harries; Ravi, Venkat (International Journal of Applied Ceramic Technology, 2008)
Simple hydroxide precursors were used for the first time for the synthesis of a typical Aurivillius compound (SrBi2Nb2O9 (SBN)) at a low temperature. This method is very advantageous because it circumvents the use of SrCO3 in the case of conventional ceramics as well in the coprecipitation methods, thereby lowering the formation of the product phase. Commercially purchased strontium hydroxide is mixed thoroughly with freshly precipitated bismuth and niobium hydroxides in a stoichiometric ratio and heated at different temperatures ranging from 100 degrees C to 750 degrees C for 12 h. The sequence of the reaction and evolution of the product phase was monitored by X-ray diffraction (XRD) studies by recording the XRD for samples calcined at different temperatures. The incipient SBN phase begins to form at temperatures as low as 400 degrees C, and phase formation was complete only at 650 degrees C as revealed by the XRD observations. The differential thermal/thermogravimetric analyses) also corroborate this result. The morphology and average particle size of these powders were investigated by transmission electron microscopy studies.

Heterogeneous cobalt-saponite catalyst for liquid phase air oxidation of p-cresol - Kshirsagar, Vikas S.; Garade, Ajit C.; Patil, Kashinath R.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2009)
Heterogeneous Co-saponite was found to be an efficient catalyst for the liquid phase oxidation of p-cresol under mild conditions. Divalent cobalt tons were found to be in both the tetrahedral and octahedral positions of the saponite clay. Studies on the effect of reaction parameters showed that the rate of reaction increased with increase in Co loading from 5 to 13% and then remained constant up to 30% of Co loading, while the rate of oxidation showed a first-order dependence on the partial pressure of oxygen up to 300 kPa. Results of oxidation experiments over Co-saponite, in an Inert atmosphere, and the XPS studies Suggest Mars-van Krevelen pathway operating, which involves lattice oxygen of Co-saponite in the liquid phase oxidation of p-cresol.

Micro-/meso-porous stannosilicate composites (Sn-MFI/MCM-41) via two-step crystallization process: process parameter-phase relationship - Niphadkar, Prashant S.; Garade, Ajit C.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V.; Joshi, Praphulla N. (Microporous and Mesoporous Materials, 2010)
Sn-MFI/MCM-41 composite material was successfully synthesized by monitoring the re-crystallization time in a simple two-step crystallization process. The length of period allowed for the recrystallization of the precursor species was found to be a controlling factor to achieve either the end members viz. Sn-MCM-41 and Sn-MFI or Sn-MFI/MCM-41 composite material. Powder XRD, FTIR, SEM, TEM, nitrogen sorption measurement, DRUV-vis and hydroxyalkylation of p-cresol reaction were used as the characterization tools. Attempts were also made to establish the relationship between type of phase formed and the process parameters such as aging time, re-crystallization temperature, time and molar ratios of TPAOH/SiO(2), CTMABr/SiO(2) and SiO(2)/SnO(2) in the gel. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: composites; Crystallization; Micro-/meso-porous stannosilicate; p-Cresol hydroxyalkylation; Sn-MCM-41; Sn-MFI

Liquid phase oxidation of p-vanillyl alcohol over synthetic Co-saponite catalyst - Garade, Ajit C.; Biradar, Narayan S.; Joshi, S. M.; Kshirsagar, V. S.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V. (Applied Clay Science, 2011)
Effect of cobalt loading on porosity of synthetic Co-saponite catalysts and on the air oxidation of p-vanillyl alcohol was studied by varying Co content in the range of 5% to 30% using in situ precipitation method. The pore size increased from 1.29 to 3.69 nm indicating a transition from micro to meso porosity, with increase in Co loading from 5% to 30%. The distribution ratio of Co(3)O(4)/CoO phases as estimated from TPR studies, also increased from 0.84 to 1.67 with increase in Co loading from 5% to 13% and remained almost constant (1.7) with further increase in Co loading up to 30%. The highest activity (conversion 55%) and selectivity of 99% to p-vanillin obtained for 13% Co-saponite in p-vanillyl alcohol oxidation was due to the highest distribution ratios of Co(3)O(4)/CoO phases. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Co-saponite; Cobalt oxide phase ratio; p-Vanillin; p-Vanillyl alcohol oxidation; Porosity transition; Temperature programmed reduction

Toward an understanding of the molecular level properties of ziegler-natta catalyst support with and without the internal electron donor - Thushara, K. S.; Gnanakumar, Edwin S.; Mathew, Renny; Jha, Ratnesh Kumar; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Sarma, Krishna; Padmanabhan, Sudhakar; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2011)
Two Ziegler-Natta catalysts supported on molecular adducts, namely, MgCl2 center dot 6EtOH (ME) and MgCl2 center dot 5EtOH center dot EtOOCPh (Est-ME), have been prepared. A systematic effort has been made to unravel the molecular level structure property relationships of the catalysts and adducts. Ethylbenzoate is an internal electron donor, and its in situ formation through EtOH+PhCOCl coupling is successfully achieved. The above adduct has been treated with TiCl4, and the resultant catalyst (Ti/Est-ME) is evaluated for ethylene polymerization activity. Rand C-13 CP/MAS NMR of Est-ME (Ti/Est-ME) show carbonyl features at 1730 (1680) cm(-1) and 169 (170) delta, respectively, providing direct support for the presence of ester as an integral part. In spite of low surface area, Ti/Est-ME gives higher yield for ethylene polymerization than the one derived from ME. The results indicate that electronic environment is more important than surface area or any other single factor in determining the polymerization activity.

Modified zeolite immobilized palladium for ligand-free suzuki-miyaura cross-coupling reaction - Kumbhar, Arjun; Kamble, Santosh; Mane, Anand; Jha, Ratnesh Kumar; Salunkhe, Rajashri (Journal of Organometallic Chemistry, 2013)
A palladium-based catalyst supported on modified ZSM-5 was successfully prepared by a facile procedure. The prepared heterogeneous catalyst Pd@desilicated ZSM-5 showed an excellent catalytic activity at very low Pd loading (0.02 mol%) for the ligand-free Suzuki-Miyaura coupling reactions of various aryl bromides affording excellent yields of the products. The prepared catalyst presents good recyclability, over four catalytic cycles. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: heterogeneous catalysis; Suzuki-Miyaura reaction; zeolite

Effect of SnO2/Al2O3 ratio of Si-based MFI on its acidity and hydrophobicity: application in selective hydroxyalkylation of p-cresol - Garade, Ajit C.; Malwadkar, A. V.; Niphadkar, P. S.; Jha, Ratnesh Kumar; Joshi, P. N.; Rode, C. V. (Catalysis Communications, 2014)
Silica based MR type molecular sieves with various SnO2/Al2O3 ratios were synthesized from gels having molar compositions SiO2:xSnO(2):yAl(2)O(3):0.23(TPA)(2)O:35H(2)O where 0 <= x <= 0.02 and 0 <= y <= 0.01. Recyclable, Al-free Sn-MFI catalyst showed 31% conversion of formaldehyde with 100% selectivity to 2,2'-methylenebis(4-methylphenol) in hydroxyalkylation of p-cresol with formaldehyde on account of moderate acidity and higher hydrophobicity. (C) 2013 Elsevier B.A. All rights reserved.
Keywords: Al-27 MAS NMR; Hydroxyalkylation; Molecular sieves; p-Cresol; Stannosilicate

Influence of starting precursors and synthesis methods on the physiochemical properties of zirconia - Gaydhankar, T. R.; Jha, Ratnesh Kumar; Nikalje, M. D.; Waghmare, K. J. (Materials Research Bulletin, 2014)
Under identical and judiciously pre-optimized synthesis conditions, the influence of different combinations of zirconium sources and/or post treatment conditions on structural properties, thermal stability, phase composition and morphology of zirconia has been investigated. High surface area tetragonal zirconia could be synthesized in a cost-effective manner from 1 M solution of zirconium oxynitrate at pH 11 using aqueous ammonia solution as a precipitant when calcined at 400 degrees C for 3 h. Irrespective of the preparation method, pH and starting precursor, zirconia samples prepared without digestion contained dominant monoclinic phase with some traces of tetragonal phase when calcined at 700 degrees C. Even though there is linear decrease in surface area with increase in the crystallite size for each sample as a function of calcination temperature, no co-relation between the surface area and crystallite size could be achieved. SEM images show agglomerated and irregular shape particles between 10 to 20 mu m. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Oxides; Sol-gel chemistry; Thermogravimetric analysis (TGA)

Role of surface synergistic effect on the performance of Ni-based hydrotalcite catalyst for highly efficient hydrogenation of furfural - Manikandan, Marimuthu; Venugopal, Ashok Kumar; Prabu, Kandasamy; Jha, Ratnesh Kumar; Thirumalaiswamy, Raja (Journal of Molecular Catalysis A-Chemical, 2016)
The selective vapor phase hydrogenation of furfural at ambient pressure has been investigated using a facile and robust hydrotalcite derived Ni containing mixed oxide catalyst. The systematic characterization results conferred that the difficulty in the reduction of Ni species due to the strong interaction between Ni and support, which facilitated from the homogeneous distribution of hydrotalcite structure. It was also found that the structure and catalytic performance of the catalysts were greatly influenced by Ni loading. Through fine-tuned surface elemental sites and reaction conditions, furfural conversion of 98% with 95% of furfuryl alcohol selectivity was achieved over a MAN-2 catalyst containing two molar ratio of Ni. The results have demonstrated that the incorporation of Mg significantly enhances the Ni-support interaction, Ni dispersion and catalytic performance. The high efficiency of the Ni-based hydrotalcite derived catalyst was mainly attributed to the surface synergistic interaction between the catalytically active metallic Ni sites and the strong basic sites, which furnished an eco-benign and sustainable catalyst for the selective hydrogenation of furfural. Furthermore, the spent catalyst analysis substantiated that no significant difference in the catalyst phase was observed even after 48 h of reaction stream. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: alcohol-hydrotalcites-selective; Biomass-frurfural-furfuryl; Hydrogenation

Temperature-controlled hydrothermal synthesis of α-MnO2 nanorods for catalytic oxidation of cyclohexanone - Jha, Ratnesh Kumar; Manikandan, Marimuthu; Prabu, Marimuthu; Vineeth, Nidhi R.; Dharmalingam, Praveen; Archana, Ramakrishnan; Harsha, Murudappa; Shankar, Sonu Ram; Bhatte, Kushal; Raja, Thirumalaiswamy (CHEMPLUSCHEM, 2024)
Keywords: Adipic Acid; conversion; MANGANESE OXIDES